The Role of Service Regulation in Pharmacy Waiting Time with Information Systems as Intervening - Yusni Sulastri; Rina Mutiara; Tjipto Rini (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
The waiting time for outpatient pharmacy services at Permata Jonggol Hospital had not met the minimum service standards, potentially reducing service quality and patient satisfaction. This issue was suspected to be influenced by human resource (HR) competence, service regulations, and the utilization of the Hospital Management Information System (HMIS). This study aimed to analyze the effect of HR competence and service regulations on pharmacy waiting time, with HMIS utilization as an intervening variable. The study used a quantitative approach with a cross-sectional design. Data were collected at a single point in time using instruments that had been tested for validity and reliability. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that HR competence, service regulations, and HMIS utilization simultaneously had a significant effect on pharmacy waiting time. Partially, HR competence and service regulations significantly affected HMIS utilization and waiting time. HMIS utilization also significantly influenced waiting time and mediated the relationship between HR competence, service regulations, and pharmacy waiting time. In conclusion, improving pharmacists’ competence, strengthening service regulations, and optimizing HMIS utilization in an integrated manner were important strategies to reduce waiting time and improve service efficiency and quality